Feasibility study of seaweed farming Kappaphycus alvarezii in Sub-District North Pulau Laut and Sub-District East Pulau Laut Kota baru Regency, South Borneo, Indonesia. Issue 1 (September 2020) - Tuwo, A; RizkaAuliana,; Samawi, M F; Aprianto, R; Tresnati, J
Abstract: Kappaphycus alvrezii has the potential to be developed due to the increasing demand for local and international markets. To support the development of Kappaphycus alvrezii cultivation, a new feasible cultivation area is needed. This study aims to analyze the feasibility of Kappaphycus alvarezii farming in North Pulau Laut District and Pulau Laut Timur District, Kotabaru Regency, South Kalimantan. The analytical method used was a spatial analysis of physical and chemical parameters and strategic environmental conditions analysis. The total area of land suitable for seaweed cultivation in Pulau Laut Utara and Kecamatan Pulau Laut Timur was around 11, 499 ha for the feasible category, with the waters carrying capacity of was 9, 498 ha for 18, 996 units of seaweed cultivation; with this carrying capacity, it can produce 79, 783 to 96, 880 tons year −1 for four times the harvest season or 99, 729 to 121, 100 tons year −1 for 5 times the harvest season. Three main strategies that need to be implemented to achieve the estimated production were improving quantity and quality of seaweed production, utilization of all suitable land for seaweed cultivation basing on the waters carrying capacity, and research development to improve the seaweed quality and products by involving universities, government, and private companies/institutions.